The Effectiveness of the Support to Development of the Islamic Higher Education Project in Improving the Quality of Education - Rahman El Junusi; Musahadi Musahadi; Ferry Khusnul Mubarrok (At-Taqaddum, 2023)
This study aims to explore the Support to Development of the Islamic Higher Education Project (SDIHE) in an effort to improve the quality of Islamic Religious Higher Educations (PTKIs). This research is a policy research conducted at UIN Sumatera Utara, UIN Raden Fatah, UIN Walisongo and UIN Mataram. It employs exploratory descriptive analysis which explains the SDIHE phenomenon. The results show that SDIHE which is run by PTKIs (UIN Sumatera Utara, UIN Raden Fatah, UIN Walisongo and UIN Mataram) through curriculum development and expert training programs is effective in improving the quality of PTKIs. SDIHE has an impact on increasing the ranking of these universities globally and locally. This shows an increase in the performance of PTKIs. There has been no research on the effectiveness and impact of projects from foreign grants in Higher Education that comprehensively discusses quality from the perspective of curriculum development and expert training programs.